Analytical Investigation of Oleic Acid Double Bond Cleavage Using Cu-BiVO4 Photocatalyst in Water/Ethanol System Using GC-MS Analysis - Annisa Aulia Rahmah; Bambang Prijamboedi; Fainan Failamani (Program Studi Kimia Universitas Negeri Jakarta, 2026)
The oxidative cleavage of unsaturated fatty acids is a promising pathway for producing value-added chemicals; however, its photocatalytic conversion remains limited by catalyst efficiency. This study investigates the performance of BiVO₄ and Cu-modified BiVO₄ (Cu–BiVO₄) in promoting the photocatalytic cleavage of oleic acid in a water–ethanol system under visible light irradiation. The catalysts were synthesized via hydrothermal and impregnation methods, followed by photocatalytic reactions for 24 h. Product distribution and transformation pathways were analyzed using GC–MS. The results show that pristine BiVO₄ exhibits limited catalytic activity, while Cu–BiVO₄ significantly enhances the formation of C14 and C16 saturated fatty acids along with various oxidative cleavage products. This improvement is attributed to enhanced charge separation and increased generation of reactive oxygen species. These findings demonstrate that Cu–BiVO₄ is a more effective photocatalyst for the oxidative transformation of unsaturated fatty acids.